Probing lewis acidity and reactivity of Sn- and Ti-beta zeolite using industrially important moieties: a periodic density functional study - Kulkarni, Bhakti S.; Krishnamurty, Sailaja; Pal, Sourav (Journal of Molecular Catalysis A-Chemical, 2010)
The Lewis acidic nature and reactivity of two industrially important catalysts, viz.. Sn and Ti substituted beta zeolite (T-BEA) are analyzed using a unique combination of structural parameters, energetics and reactivity descriptors. To achieve this purpose, we adsorb the industrially important moieties (L) namely NH(3), H(2)O, CH(3)OH, CH(3)CN on the active sites of T-BEA. The calculations were performed using a periodic density functional method where the valence electrons are described using a plane wave basis set in conjunction with pseudo-potentials for the core electrons. The analysis of the structural properties of these complexes reveals that TO(4) shows typical characteristic splitting 120 degrees/90 degrees, close to bipyramidal geometry as compared to tetrahedral symmetry observed in the bare T-BEA. This is associated with small variations in the framework bond lengths (>= 0.08 angstrom) and a substantially large variation of bond angles (<= 10 degrees) in all the ligand-zeolite complexes. Further in both cases of Sn and Ti substituted beta zeolite, ligand interacts at optimum inter-atomic bond distance. Our interaction energies show that adsorption of all ligand moieties is stronger at Sn center than that of Ti. In general, the order of stability of the different T-BEA adducts is NH(3) > H(2)O > CH(3)OH > CH(3)CN. The ligand interaction is associated with the corresponding bond elongation and bond reduction of the adsorbed molecules on catalyst active site, which can be taken as measure of red or blue shifted frequencies. Finally, the global descriptors of reactivity justify the fact that soft acid, Sn-BEA, interacts strongly with soft bases following the Pearson's HSAB principle. However, hard acid, Ti-BEA interacts with soft bases to form a stable Lewis adduct. Furthermore, the HOMO-LUMO gap of all Sn-BEA-L adducts is lower than that of Ti-BEA-L adducts indicating to its higher Lewis acidic nature compared to Ti-BEA. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Beta zeolite; Lewis acidity; Ligand-zeolite complex; Periodic-DFT; Reactivity descriptors